Efficiency Of Natural Resources And Carbon Dioxide In Asean-6 - Cacak Rinunate; Aliasuddin; Ernawati (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
This study analyzes the effect of natural resource efficiency, renewable energy, ICT, and economic growth on carbon dioxide (CO?) emissions in ASEAN-6 countries, namely Indonesia, Malaysia, Thailand, the Philippines, Vietnam, and Singapore. This study uses panel data for the period 1990-2023 and is analyzed using the panel Autoregressive Distributed Lag (ARDL method to estimate the short-term and long-term relationships between variables. The results show that in the long term, natural resource efficiency and renewable energy tend to play a role in reducing CO? emissions, while ICT and economic growth show varying relationships depending on the economic structure and level of development of each country. In the short term, carbon emission dynamics are influenced by changes in economic activity, energy utilization, and the intensity of digital technology use. These findings provide an understanding that efforts to reduce carbon emissions in ASEAN-6 cannot rely on a single factor, but require synergy between increasing resource efficiency, accelerating the renewable energy transition, utilizing environmentally friendly ICT, and managing sustainable economic growth. Therefore, this study recommends strengthening integrated low-carbon development policies to support climate change mitigation commitments without hampering regional economic growth.